ENHANCING KNOWLEDGE AND AWARENESS FOR MEASLES AND RUBELLA ELIMINATION TO PREVENT CONGENITAL RUBELLA SYNDROME IN KULON PROGO AND GUNUNGKIDUL REGENCIES - Herini, Elisabeth Siti; Triono, Agung; Iskandar, Kristy; Indrawanti, Ratni; Sitaresmi, Mei Neni; Nuady, Albaaza; Prasetyo, Ashadi; Paramastuti, Avianti; Nugrahanto, Andika Priamas; Mooiindie, Khansadhia Hasmaradana; Damroni, Rais Aliffandy; Timoti, Joshua (Universitas Airlangga, 2024)
Introduction: Measles-Rubella (MR) Vaccination coverage is important in eliminating Congenital Rubella Syndrome (CRS). In 2023, Kulon Progo and Gunungkidul Regencies recorded 98.59% and 97.63%, respectively. We conducted campaign activities, introduced the Measles-Rubella (MR) vaccine, and implemented educational efforts crucial for controlling measles, rubella and CRS. A collaborative educational program was organized to improve the quality of promotive and preventive education provided to health workers and elementary teachers. Aims: To enhance the knowledge of health workers and elementary teachers regarding measles, rubella, CRS and elimination strategies in Kulon Progo and Gunungkidul Regency. Methods: This study employed a quasi-experimental, non-randomized design with no control group. The participants were selected from all primary health care centers and selected elementary schools in Kulon Progo and Gunungkidul Regency. Before and after a multi-modal educational program, knowledge of participants was measured using questionnaire and analyzed using Wilcoxon signed-rank test. Results: We included 72 health workers and 8 elementary teachers in Kulon Progo and Gunungkidul Regency. The results indicated an increase in knowledge among health workers regarding these topics. However, elementary teachers did not demonstrate statistically significant improvements in knowledge level, likely due to the small number of participants and a general lack of knowledge about these subjects among teachers. Conclusion: Multi-modal intervention enhanced the knowledge of health workers and elementary teachers about measles, rubella, CRS, elimination strategies of these diseases in two regencies of the Special Region of Yogyakarta. Therefore, it is essential that public health authorities should prioritize continuous and accessible education programs for them